Edukasi Berdasarkan Status IMT Prahamil Dalam Upaya Peningkatan Berat Badan Ibu Hamil - Rini Sulistiawati; Henny Fitriani; Affi Zakiyya (POLTEKKES KEMENKES MANADO, 2022)
Background: The status of pregnant women through BMI according to Riskesdas data is abnormal (thin, fat and obese) greater than that of men, this will have an impact on the mother and the process of fetal growth. Therefore, as an effort to detect this problem early, monitoring the weight gain of pregnant women is based on the pre-pregnancy Body Mass Index (BMI). Weight gain during pregnancy indicates the nutritional status of the mother. Objective: To determine the effectiveness of education based on the nutritional status of pre-pregnancy BMI on the suitability of increasing pregnant women's weight. Methods: quasi-experimental research design, non-equivalent group with posttest only with control group design conducted on 156 pregnant women in the working area of ​​the Public Health Center of Perumnas 2 and the UPTD of the South Pontianak Health Center. The sampling technique used is consecutive sampling. Results: Based on statistical tests, it was shown that education was effective on the suitability of weight gain for pregnant women based on the nutritional status of pre-pregnancy BMI with p value = 0.001 (p value <0.05). As a recommendation, specific education based on the nutritional status of pre-pregnancy BMI can be applied in health facilities in an effort to increase the weight of pregnant women.